STRATEGI PEMBELAJARAN EKSTRAKULIKULER TEATER DALAM MENGEMBANGKAN SENI PERAN SISWA DI SMP ISLAM AL-AMAL: strategi pembelajaran ekstrakurikuler - Khoirul Anam, Moch (Global Action and Education for Society, 2026)
Education in the 21st century requires the development of holistic skills, including creativity, collaboration, communication, and critical thinking. Extracurricular drama has great potential as a vehicle for developing these skills, but at Al-Amal Islamic Junior High School in Surabaya, its development is hampered by a lack of systematic and collaborative learning strategies. This qualitative case study aims to examine the performing arts extracurricular learning strategies implemented, analyze the obstacles encountered, and develop a cooperative learning-based strategy model. Data were collected through observation, interviews, and documentation studies. The results show that the application of cooperative learning with elements such as group-based role-play, character interpretation discussions, and peer teaching has proven effective not only in improving students' acting skills but also in fostering self-confidence, creativity, solidarity, and communication skills. The success of this strategy is also demonstrated by the students' achievement in winning a regional theater competition. This study concludes that cooperative learning is a relevant and applicable strategy for optimizing the role of acting extracurricular activities in shaping students' 21st-century skills and character.